An updated bird checklist for Dharan Forests Important Bird and Biodiversity Area, Nepal (Nepalese Journal of Zoology, 2025)
An eleven-day bird survey carried out in Dharan Forests Important Bird and Biodiversity Area (DFIBA) in February 2025 recorded 180 species. This was followed by a desk study extracting records from published and unpublished reports, and eBird. These records were used to produce the first published DFIBA checklist. A total of 390 species was recorded between January 1949 and 17 September 2025, including four additional species from this bird survey and 46 additional species from the desk study. In 2024, DFIBA was assessed as an IBA based on globally threatened species and characteristic biome species criteria. This study showed that nine globally threatened species have been recorded, but four have not been found for at least 25 years, five are now rare and two have been downlisted, so DFIBA no longer qualifies as an IBA based on the globally threatened criterion. However, DFIBA still qualifies as an IBA based on the biome-restricted criterion. Three additional species were recorded in the Indo-Malayan Tropical Dry Zone biome than in the previous assessment. A total of 21 bird species, 65 per cent of the species recorded in this biome in Nepal was found, so slightly strengthening the evidence that DFIBA qualifies based on the biome-restricted assemblage criterion. The 2025 survey was limited to areas close to forest edges because of high elephant activity throughout the DFIBA. Designation of the DFIBA as a protected area is highly recommended. This would protect the tropical evergreen forest, which in Nepal, only occurs outside the protected area system, in DFIBA and the Mai valley IBA. It would also facilitate management to improve DFIBA habitats for wildlife. DFIBA remains significantly under-recorded. Further bird surveys in the centre and east, at higher elevations to cover the full altitudinal range and in all seasons should increase the DFIBA species list.